Maghemite (hematite) core (shell) nanorods via thermolysis of a molecular solid of Fe-complex - Chaudhari, N. S.; Warule, S. S.; Muduli, Subas; Kale, B. B.; Jouen, Samuel; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Dalton Transactions, 2011)
An Fe-metal complex with 2'-hydroxy chalcone (2'-HC) ligands [Fe(III) (2'-hydroxy chalcone) 3] is synthesized by a chemical route and is subjected to different thermal treatments. Upon thermolysis in air at 450 degrees C for 3 h the complex yields maghemite (gamma-Fe(2)O(3)) nanorods with a thin hematite (alpha-Fe(2)O(3)) shell. X-Ray diffraction (XRD), Mossbauer spectroscopy, diffuse reflectance spectroscopy (UV-DRS), high resolution transmission electron microscopy (HR-TEM), field emission scanning electron microscopy (FE-SEM) and vibrating sample magnetometry (VSM) are used to characterize the samples. The stability of the ligand and the Fe-complex is further examined by using thermogravimmetric/differential thermal analysis (TGA/DTA). We suggest a residual ligand controlled mechanism for the formation of an anisotropic nanostructure in a crumbling molecular solid undergoing ligand decomposition. Since the band gap of iron oxide is in the visible range, we explored the use of our core shell nano-rod sample for photocatalytic activity for H(2) generation by H(2)S splitting under solar light. We observed high photocatalytic activity for hydrogen generation (75 ml h(-1)).

Magnetic properties of nanocrystalline CoFe2O4 synthesized by thermal plasma in large scale - Nawale, A. B.; Kanhe, Nilesh S.; Patil, K. R.; Reddy, V. R.; Gupta, A.; Kale, B. B.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Materials Chemistry and Physics, 2012)
The paper reports the large scale synthesis of nanoparticles of CoFe2O4 using thermal plasma reactor by gas phase condensation method. The yield of formation was found to be around 15 g h(-1). The magnetic properties of CoFe2O4, synthesized at different reactor powers, were investigated in view of studying the effect of operating parameters of plasma reactor on the structural reorganization leading to the different cation distribution. The values of saturation magnetization, coercivity and remanent magnetization were found to be influenced by input power in thermal plasma. Although the increase in saturation magnetization was marginal (61 emu g(-1) to 70 emu g(-1)) with increasing plasma power; a significant increase in the coercivity (552 Oe to 849 Oe) and remanent magnetization (16 emu g(-1) to 26 emu g(-1)) were also noticed. The Mossbauer spectra showed mixed spinel structure and canted spin order for the as synthesized nanoparticles. The detailed analysis of cation distribution using the Mossbauer spectroscopy and X-ray photoelectron spectroscopy leads to the conclusion that the sample synthesized at an optimized power shows the different site selective states. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic materials; magnetic properties; Mossbauer spectroscopy; Nanostructures